Production of Chicken Patties Supplemented with Cantaloupe By-Products: Impact on the Quality, Storage Stability, and Antioxidant Activity - Maha IK Ali; Rehab Mohamed Ibrahim; Aliaa G. M. Mostafa (International Journal of Food Science)
This study investigated the effect of supplementation with cantaloupe peel (CP) and seeds (CS) (3, 6, 9, and 12%) powder on the quality and antioxidant activity of raw and cooked chicken patties during storage (-20°C/3 months). The addition of CP and CS powder increased protein, fat, ash, and fiber values of chicken patties compared with control, while carbohydrate, pH, and TBA were decreased at zero time and after 3 months of storage. The WHC, cooking yield, fat retention, and moisture retention were increased by increasing CP and CS powder addition ratios, while cooking loss and shrinkage were decreased. Also, CP and CS powder improved antioxidant activity, microbiological quality, and overall acceptability of chicken patties. The hardness of raw and cooked chicken patties was decreased with increasing CP and CS addition ratios. It is recommended to use CP and CS powder as functional ingredients in the preparation of functional foods.